Nepal Development Update, September 2017 : Fiscal Architecture for Federal Nepal - World Bank (World Bank, Washington, DC, 2017)
Global growth is picking up and the growth in the South Asia region continues to remain strong. A recovery in industrial activity has coincided with a pickup in global trade, after two years of marked weakness. Growth in South Asia remains strong, with regional output projected to grow by 6.8 percent in 2017 and an average of 7.2 percent in 2018–19. Economic activity in Nepal, which rebounded strongly in FY2017, reaching 7.5 percent (year-over-year [y/y]) following two challenging years, has again been impacted by severe flood affecting more than one-third of the country. High inflation in the last two years induced by disruptions moderated sharply by early 2017 and further slowed, reaching decade-low inflation by the end of FY2017, due to moderating inflation in India.